1982
DOI: 10.1104/pp.69.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Regulatory Properties of Mung Bean (Vigna Radiata L.) Serine Hydroxymethyltransferase

Abstract: Serine hydroxymethyltransferase, the rirst enzyme in the pathway for interconversion of C1 fragments, was purified to homogeneity for the first time from any plant source. The enzyme from 72-h mung bean (Vigna radiata L.) seedlings was isolated using Blue Sepharose CL-6B and folate-AH-Sepharose4B affinity matrices and had the highest specific activity (1. The sigmoid saturation pattern of H4folate (nH = 2.0), one of the substrates, the abolition of sigmoidicity by NADH, an allosteric positive effector (nH = 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
1

Year Published

1983
1983
2003
2003

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 6 publications
1
11
0
1
Order By: Relevance
“…Blue Sepharose CL-6B and Folate AH-Sepharose, and a hydroxylapatite column gave a preparation with a specific activity of 7.8 nmol (mg protein) ' min ' (Tab. I) which is similar to the specific activity reported for the rabbit liver SHMT [ 10 nmol (mg protein)"' min ';Schirch et al 1985] but significantly higher than the mung bean enzyme [1.33 ixmol (mg protein) ' min '; Rao and Rao 1982).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Blue Sepharose CL-6B and Folate AH-Sepharose, and a hydroxylapatite column gave a preparation with a specific activity of 7.8 nmol (mg protein) ' min ' (Tab. I) which is similar to the specific activity reported for the rabbit liver SHMT [ 10 nmol (mg protein)"' min ';Schirch et al 1985] but significantly higher than the mung bean enzyme [1.33 ixmol (mg protein) ' min '; Rao and Rao 1982).…”
Section: Resultssupporting
confidence: 86%
“…An improved knowledge of this mitochondrial enzyme could give us a better understanding of photorespiration. SHMT has been purified and characterized from various non-photosynthetic sources (O'Connor and Hanson 1975, Rao and Rao 1982, Schirch 1982, Schirch et al 1985. It is of interest to see if this plant enzyme behaves in a similar way as, for example, its mammalian counterpart for which the reaction is generally believed to be most significant in the direction from serine to glycine (Schirch 1982), which is the opposite direction compared to photorespiration.…”
Section: Introductionmentioning
confidence: 99%
“…There are two reports on the relationship between these antibiotics and eukaryotic plant enzymes. The antibiotic D-cycloserine inhibits the activity of serine hydroxymethyltransferase isolated from mung bean seedlings (Rao and Rao 1982). Mújica-Jiménez et al (1998) reported that fosfomycin acts as a potent, reversible non-essential activator of phosphoenolpyruvate carboxylase from C 4 maize leaves by binding to the same allosteric site as glucose-6-phosphate.…”
mentioning
confidence: 99%
“…Dans les mitochondries, la condensation de 2 molécules de glycine, catalysée par la sérine hydroxyméthyltransférase, aboutit à la sérine (folbert, 1979;Rao et Rao, 1982) ; dans cette réaction une molécule de C0 2 et une de NH 3 sont libérées; le C0 2 est émis à l'extérieur en atmosphère sans gaz carbonique ou recyclé dans le métabolisme photosynthétique en air normal (Gaudillère, 1981) ; l'ammonium est immédiatement repris par le jeu de la glutamine synthétase-glutamate synthase étudié dans le paragraphe précé-dent. Lips (1979) traite de la photorespiration dans le métabolisme des nitrates.…”
Section: B -Synthèse D'autres Composés Azotésunclassified